Dromia Weber 1795 - TAVARES, MARCOS; MENDONÇA, JOEL BRAGA DE JR. (Zenodo, 2022)
Genus Dromia Weber, 1795 Type species. Cancer personatus Linnaeus, 1758: 628 [Type locality: unknown]. Remarks. Dromia sensu McLay (2009) is exclusively Atlantic/Mediterranean in distribution. Dromia gouveai Melo & Campos Junior, 1999 from Brazil was merged into the synonymy of D. erythropus by McLay (2009) based on a personal communication by M. Tavares. A discussion on the identity of D. gouveai is now given. Published as part of TAVARES, MARCOS & MENDONÇA, JOEL BRAGA DE JR., 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 (1) on page 13, DOI:10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155